Investigating the effects of visual deprivation on subcortical and cortical structures using functional MRI and MR spectroscopy - Coullon, G (2015)
Visual deprivation in early life causes widespread changes to the visual pathway. Structures normally dedicated to vision can be recruited for processing of the remaining senses (i.e. audition). This thesis used magnetic resonance imaging to explore how the 'visual' pathway reorganises in congenital bilateral anophthalmia, a condition where individuals are born without eyes. Anophthalmia provides a unique model of complete deprivation, since the ‘visual’ pathway has not experienced pre- or post-natal visual input. Firstly, this thesis explored reorganisation of the anophthalmic 'visual' pathway for auditory processing, from subcortical structures responding to basic sounds (Chapters 3 and 4), to higher-order occipital areas extracting meaning from speech sounds (Chapter 7). Secondly, this thesis looked to better understand the neurochemical, neuroanatomical and behavioural changes that accompany reorganisation in anophthalmia (Chapters 5 and 6). Finally, this thesis investigated whether similar changes can take place in the sighted brain after a short period of visual deprivation (Chapter 8). The experiments in this thesis provide some evidence that the lack of pre-natal visual experiences affects cross-modal reorganisation. Chapter 4 describes a unique subcortico-cortical route for auditory input in anophthalmia. Furthermore, Chapter 7 suggests that hierarchical processing of sensory information in the occipital cortex is maintained in anophthalmia, which may not be the case in congenital or early-onset blindness. However, this thesis also suggests that some reorganisation thought to be limited to anophthalmia can be found in early-onset blindness, for example with the subcortical functional changes described in Chapter 3. In addition, neurochemical, neuroanatomical and behavioural changes described in Chapters 5 and 6 are comparable to those reported in early-onset blindness, therefore demonstrating important similarities between these populations. Finally, this thesis describes how some of these functional and behavioural changes can also take place in sighted subjects after a short period of blindfolding, although this effect is extremely variable across subjects (Chapter 8). The thesis concludes by highlighting the considerable contribution of individual differences in studies of cross-modal reorganisation, and emphasises the need for larger more homogenous groups when investigating subcortical and cortical plasticity in the absence of visual input.